IMPACT ANALYSIS OF COAL MINING ON WATER POLLUTION IN BUNATI VILLAGE, ANGSANA SUB-DISTRICT, TANAH BUMBU REGENCY, SOUTH KALIMANTAN - Kasim, Hasni; Haslinda, Haslinda; Yusuf, Muh; Rachmat, Rachmat; Basmar, Muh. Fahmi (INFOKUM, 2022)
The purpose of this study was to analyze the heavy metal mercury (Hg) component in coal mining waste water during mining activities. A field observation method has been used to continuously capture and monitor sampling at mining and processing sites. In the laboratory, tests for the content of metal mercury (Hg) in liquid waste from mine waste have been completed. The three components of the field survey are preliminary research, main research (sampling), and laboratory analysis. Air samples were fired at pre-tapped points based on waste conditions while fully appreciating the potential of about four points. The results showed that there were two air samples with very high mercury content, namely 5.0828 pp Hg at location 02 (ST.02) and 6.3060 pp Hg at location 3 (ST.03).